Identification of a Prognostic Signature Associated With the Homeobox Gene Family for Bladder Cancer - Dong, Bingqi; Liang, Jiaming; Li, Ding; Song, Wenping; Song, Jinbo; Zhu, Mingkai; Zhao, Shiming; Ma, Yongkang; Yang, Tiejun (Frontiers in Molecular Biosciences, 2021)
Background: Bladder cancer (BLCA) is a common malignant tumor of the genitourinary system, and there is a lack of specific, reliable and noninvasive tumor biomarker tests for diagnosis and prognosis evaluation. Homeobox genes play a vital role in BLCA tumorigenesis and development, but few studies have focused on the prognostic value of homeobox genes in BLCA. In this study, we aim to develop a prognostic signature associated with the homeobox gene family for BLCA. Methods: The RNA sequencing data, clinical data and probe annotation files of BLCA patients were downloaded from the Gene Expression Omnibus (GEO) database and the University of California, Santa Cruz (UCSC) Xena Browser. First, differentially expressed homeobox gene screening between tumor and normal samples was performed using the “limma” and RobustRankAggregation (RRA) methods. The mutation data were obtained with the “TCGAmutation” package and visualized with the “maftools” package. Kaplan-Meier curves were plotted with the “survminer” package. Then, a signature was constructed by logistic regression analysis. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses were performed using “clusterProfiler”. Furthermore, the infiltration level of each immune cell type was estimated using the single-sample gene set enrichment analysis (ssGSEA) algorithm. Finally, the performance of the signature was evaluated by receiver operating characteristic (ROC) curve and calibration curve analyses. Results: Six genes were selected to construct this prognostic model: TSHZ3, ZFHX4, ZEB2, MEIS1, ISL1, and HOXC4. We divided the BLCA cohort into high- and low-risk groups based on the median risk score calculated with the novel signature. The overall survival (OS) rate of the high-risk group was significantly lower than that of the low-risk group. The infiltration levels of almost all immune cells were significantly higher in the high-risk group than in the low-risk group. The average risk score for the group that responded to immunotherapy was significantly lower than that of the group that did not. Conclusions: We constructed a risk prediction signature with 6 homeobox genes, which showed good accuracy and consistency in predicting patient’s prognosis and response to immunotherapy. Therefore, this signature can be a potential biomarker and treatment target for BLCA patients.